Peningkatan Kemampuan Literasi Siswa Sekolah Dasar Menggunakan Media Pembelajaran Flashcard Guna Mempercepat Penambahan Kosakata di SD Sukosari Kecamatan Kartoharjo Kota Madiun - Budiyono, Budiyono; Nuswantari, Nuswantari; Aurell, Yuendzi Santa (LP. Ma'arif Janggan Magetan, 2023)
The literacy skills of elementary school students at SDN Sukosari are very low, this can be seen from the students' ability to read writing, which still uses the spelling of basic letters one by one combined. This condition is quite worrying considering that the school is located in the Madiun City area, because of this, efforts need to be made to overcome it so that students are not left behind in their pursuit of understanding knowledge. The aim of this research is to determine students' literacy levels and provide treatment through flashcard learning media. This research method uses classroom action research which includes planning, implementation, observation and reflection carried out through two cycles and in collaboration with school teachers. The results of the research show that flashcard learning media can improve the literacy skills of elementary school students because this media makes it easier for students to get to know the pictures on the cards more quickly, thereby strengthening their memory of the vocabulary, so flashcards as a tool to increase new vocabulary can be accelerate students' literacy skills.